2012
DOI: 10.1111/are.12061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diets supplemented with either individual or combined probiotics,Bacillus subtilisE20 andLactobacillus plantarum7-40, on the immune response and disease resistance of the mud crab,Scylla paramamosain(Estampador)

Abstract: Effects of diets supplemented with either individual or combined probiotics, Bacillus subtilis E20 and Lactobacillus plantarum 7-40, on the immune response and disease resistance of the mud crab, Scylla paramamosain (Estampador) Abstract Two trials, including firstly, diets incorporating individual or combined species of probiotics, Bacillus subtilis E20 and Lactobacillus plantarum 7-40, were fed to the mud crab, Scylla paramamosian, for 28 days to evaluate the growth, immunity and disease resistance, and seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
1
20
0
1
Order By: Relevance
“…The improved growth performance caused by BS administration was also reported in shrimp (Sadat Hoseini Madani, Adorian, Ghafari Farsani, & Hoseinifar, ) and sea cucumber ( Apostichopus japonicas ; Zhao et al, ). However, the administration of BS in large yellow croaker and mud crab ( Scylla paramamosain ) diets showed no remarkable effects on growth performance (Ai et al, ; Yeh, Chiu, Shiu, Huang, & Liu, ). The growth‐enhancing effect of BS in this study was mainly because of an improved feed utilization efficiency shown in FCR and PER, which is in agreement with many previous studies (Ai et al, ; Bagheri, Hedayati, Yavari, Alizade, & Farzanfar, ).…”
Section: Discussionmentioning
confidence: 99%
“…The improved growth performance caused by BS administration was also reported in shrimp (Sadat Hoseini Madani, Adorian, Ghafari Farsani, & Hoseinifar, ) and sea cucumber ( Apostichopus japonicas ; Zhao et al, ). However, the administration of BS in large yellow croaker and mud crab ( Scylla paramamosain ) diets showed no remarkable effects on growth performance (Ai et al, ; Yeh, Chiu, Shiu, Huang, & Liu, ). The growth‐enhancing effect of BS in this study was mainly because of an improved feed utilization efficiency shown in FCR and PER, which is in agreement with many previous studies (Ai et al, ; Bagheri, Hedayati, Yavari, Alizade, & Farzanfar, ).…”
Section: Discussionmentioning
confidence: 99%
“…plantarum 7–40 were examined for ability to induce bacterial enzyme activities, including protease, leu‐aminopeptidase and β‐galactosidase. In addition, the selected prebiotics were also investigated for supporting the growth of pathogenic bacteria, including V. alginolyticus (Liu, Cheng, Hsu, & Chen, ) and V. parahaemolyticus (Yeh, Chiu, Shiu, Huang, & Liu, ), as references. GOS, which was able to induce higher production of enzyme activity of a probiotic and exhibited significantly lower support for the growth of pathogenic bacteria, was used to formulate a synbiotic with Lac.…”
Section: Methodsmentioning
confidence: 99%
“…plantarum 7-40 were examined for ability to induce bacterial enzyme activities, including protease, leu-aminopeptidase and b-galactosidase. In addition, the selected prebiotics were also investigated for supporting the growth of pathogenic bacteria, including V. alginolyticus (Liu, Cheng, Hsu, & Chen, 2004) and V. parahaemolyticus (Yeh, Chiu, Shiu, Huang, & Liu, 2014), as references.…”
Section: Experimental Designmentioning
confidence: 99%
“…There are a few reports on some compounds derived from Bacillus species inhibiting bacterial biofilms in general (Rivardo et al 2009;Nithya, Devi & Pandian 2011). The members of this genus have also been used for improving the health of aqua cultured species such as Fenneropenaeus indicus, Penaeus vannamei, Macrobrachium rosenbergii, Crassostrea virginica, Ctenopharyngodon idellus and Scylla paramamosain (Ziaei-Nejad, Rezaei, Takami, Lovett, Mirvaghefi & Shakouri 2006;Zhou, Wang & Li 2009;Rahiman, Jesmi, Thomas & Hatha 2010;Karim, Zhao, Rowley, Nelson & Gomez-Chiarri 2013;Zhang, Fu, Deng, Liang, Zheng, Sun, Zhu, Peng, Wang, Wenying & Li 2013;Yeh, Chiu, Shiu, Huang & Liu 2014). In the current investigation, we have shown the effectiveness of the CFS derived from B. licheniformis D1 in controlling and disrupting aquaculture associated pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%